The Circular Economy in Terms of Zinc Recovery from Industrial Waste – Directions for the Development and Profitability of Recycling - Bobrowski, Artur; Nejranowski, Aleksander (Journal of Casting & Materials Engineering, 2023)
The article reviews the current state of the art in the field of zinc recycling. The results of model studies of the profitability (profitability) of the process of zinc recovery in precipitation in the form of dusts and sludges are presented. The cost of purchasing waste and the necessary energy and material expenditures were taken into account. It has been shown that access to a cheap source of waste is essential for the profitability of the zinc recovery process.